MANAGEMENT OF ACUTE LIMB ISCHEMIA - THE REVIEW - Jędrzej Kęsik; Aleksandra Kaźmierczyk; Daria Madycka; Małgorzata Słaboń; Karol Stępniak; Wiktor Telega; Kinga Wnuczek; Joanna Wrona; Weronika Skrzypek; Julia Czerwik (International Journal of Innovative Technologies in Social Science, 2025)
Acute limb ischemia (ALI) is a sudden reduction in limb perfusion that threatens limb viability and requires urgent intervention. It can present as an acute manifestation of peripheral arterial disease (PAD) or as an acute event in previously asymptomatic patients. This review outlines the epidemiology, pathophysiology, clinical features, diagnostic approaches, and current treatment strategies for ALI. Emphasis is placed on differentiating thrombotic and embolic causes, the use of imaging modalities such as CT angiography and duplex ultrasonography, and the application of the Rutherford classification to guide treatment decisions. Immediate systemic anticoagulation remains the cornerstone of early management, followed by either surgical revascularization or endovascular therapies. While open surgery remains standard in many cases, newer percutaneous mechanical thrombectomy systems (PMT) have emerged as effective alternatives, particularly in patients with contraindications to surgery or thrombolysis. Despite advances in diagnosis and therapy, ALI continues to carry a high risk of amputation and mortality.